In a World Characterized by Transience and Doomed to Extinction Some Old Women Still Need Love —Mrs Rooney from Samuel Beckett’s All That Fall - Uchman, Jadwiga (Text Matters: A Journal of Literature, Theory and Culture, 2013)
The article analyzes the world of transience, deterioration and death characteristic of Boghill, the place of action of Samuel Beckett’s short radio play—All That Fall. In a broadcast drama, existence is equivalent to being heard, the idea skilfully employed and commented upon by the playwright. The characters actually heard in the play are in most cases elderly or quite old and even the two young ones appear in the context of death. Numerous off-the-air individuals are dead, sterile or suffering from different illnesses. The two main characters’ situation is not different—Mr Rooney is blind, and his wife, Maddy, complains of many ailments. She is a woman in her seventies, overweight and having different kinds of health problems and thus, several times in the course of the play she expresses a wish to die. At the same time, however, in encounters with men on her way to the station she speaks in a manner characterized by numerous sexual innuendos. Furthermore, she expresses a strong yearning for love and hopes her unloving husband would show her some warm feelings. Thus she becomes a convincing illustration of Georges Bataille’s argument: “Eroticism, it may be said, is assenting to life up to the point of death” (11).